2016
DOI: 10.1177/0218492316663359
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine and ketamine for stable hemodynamics in off-pump coronary artery bypass

Abstract: Combined low-dose clonidine and ketamine produced perioperative sedation and effective suppression of sympathetic response with stable hemodynamics. Intraoperative beta-blocker use was reduced without increasing inotrope requirement. This combination prolonged the analgesic effect of opioids, reducing postoperative pain score and analgesic requirement. Low-dose clonidine alone produced sedation but did not completely block sympathetic response. Intensive care unit stay and patient outcome were not affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It was reported that the combination of ketamine and clonidine was more effective than the nebulization of ketamine alone and caused no serious adverse effects including hemodynamic instability (Shekhar et al, 2019 ). Jigar Patel et al also found that combined low-dose clonidine and ketamine-induced perioperative sedation and effective suppression of sympathetic response with stable hemodynamics (Patel et al, 2016 ). This study also showed that the combination of Dex and Esk could synergically enhance each other in sedation and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the combination of ketamine and clonidine was more effective than the nebulization of ketamine alone and caused no serious adverse effects including hemodynamic instability (Shekhar et al, 2019 ). Jigar Patel et al also found that combined low-dose clonidine and ketamine-induced perioperative sedation and effective suppression of sympathetic response with stable hemodynamics (Patel et al, 2016 ). This study also showed that the combination of Dex and Esk could synergically enhance each other in sedation and analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT investigating intravenous clonidine alone and in combination with ketamine versus a placebo described stable intraoperative hemodynamics as well as increased sedation scores and decreased pain scores postoperatively after bypass surgery, although the statistical significance of the difference was not reported (category D evidence). 91 The literature supported the perioperative use of intravenous dexmedetomidine as an analgesic adjunct for patients undergoing cardiac surgery as it reduced pain scores 92 and/or opioid consumption [92][93][94] as well as decreased extubation time 93 and ICU/ hospital 93 LOS (category A2-B evidence 92,93 /category B1-B evidence 94 ).…”
Section: Literaturementioning
confidence: 98%
“…One RCT investigating intravenous clonidine alone and in combination with ketamine versus a placebo described stable intraoperative hemodynamics as well as increased sedation scores and decreased pain scores postoperatively after bypass surgery, although the statistical significance of the difference was not reported (category D evidence). 91…”
Section: Intraoperative Managementmentioning
confidence: 99%
“…Journal of Anesthesia & Intensive Care Medicine trunk [10], the formation of controlled hypotension [11], use of local vasoconstrictor agents like epinephrine and phenylephrine [12], and use of premeditations [13]. Clonidine is an alpha-2 adrenergic agonist [14] and an antihypertensive agent which plays its role mainly by suppressing sympathetic activity [15], and causes central regulation of vasoconstrictor tone [16]. Studies have approved the effect of clonidine premedication before anesthesia in reducing bleeding in otolaryngology surgeries [17,18].…”
mentioning
confidence: 99%